Is vitamin D deficiency in obese youth a risk factor for less weight loss during a weight loss program?. Issue 11 (November 2019) - Van De Maele, Karolien; De Schepper, Jean; Vanbesien, Jesse; Van Helvoirt, Monique; De Guchtenaere, Ann; Gies, Inge
Abstract : Background: Vitamin D deficiency is common in obese adolescents and a risk factor for insulin resistance. We investigated if prevailing serum 25-OH vitamin D might predict the body fat loss in a group of obese adolescents undergoing a residential weight loss program. Methods: In 92 (35 male) obese adolescents (aged 10.6–19 years) undergoing a residential weight loss program in Belgium, fasting serum 25-OH vitamin D (25-OH-D), insulin, glucose and lipid levels were measured and body composition was assessed by dual-energy X-ray absorptiometry (DXA). Results: Baseline median (range) serum 25-OH-D level was 17.7 µg/L (3.8–41.8). In total, 55 adolescents had a serum 25-OH-D below 20 µg/L. In 31 adolescents with a low baseline 25-OH-D level, median increase in serum 25-OH-D was 2.4 µg/L (−4.2 to 7.2) after 10 months. This resulted in normal 25-OH-D levels in seven adolescents, whereas median BMI decreased with 1.0 SDS and body fat percentage diminished with 9.9%. Obese adolescents with or without a 25-OH-D level below or above 20 µg/L at baseline had similar changes in body weight, BMI SDS, body fat percentage and body fat mass at the end of the program. The change in serum 25-OH-D did not correlate with change in serum insulin, BMI SDS or body fat percentage and body fat mass. Conclusion: Vitamin D deficiency was present in 55 out of 92 obese adolescents at the start of the summer. Serum 25-OH-D concentration did not predict changes in body fat loss after a residential weight loss program.